2019
DOI: 10.1007/978-3-030-00069-1_17
|View full text |Cite
|
Sign up to set email alerts
|

Ptychography

Abstract: Ptychography is a computational imaging technique. A detector records an extensive data set consisting of many inference patterns obtained as an object is displaced to various positions relative to an illumination field. A computer algorithm of some type is then used to invert this data into an image. It has three key advantages: it does not depend upon a good-quality lens, or indeed on using any lens at all; it can obtain the image wave in phase as well as in intensity; and it can self-calibrate in the sense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(52 citation statements)
references
References 128 publications
(221 reference statements)
0
52
0
Order By: Relevance
“…In particular, a spatial resolution of 0.51 µm was achieved for InP nanowires 23 , much higher than in conventional detectors with pixel sizes of tens of microns 26 . Yet, in order to reach such a resolution, sophisticated and computationally demanding ptychographic reconstruction techniques 27 were required.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, a spatial resolution of 0.51 µm was achieved for InP nanowires 23 , much higher than in conventional detectors with pixel sizes of tens of microns 26 . Yet, in order to reach such a resolution, sophisticated and computationally demanding ptychographic reconstruction techniques 27 were required.…”
Section: Resultsmentioning
confidence: 99%
“…Since its first demonstration, a number of alternative reconstruction algorithms have been proposed to improve the reconstructed image quality and speed. A careful presentation of different ptychography algorithms and their advantages and benchmarks are outside of this review's scope, but may be found elsewhere in the literature [19,[71][72][73][74]. Readers interested in learning about the reconstruction process in more detail should refer to [75] which provides detailed steps along with some Matlab tutorials.…”
Section: Computational Reconstructionmentioning
confidence: 99%
“…Properties of a ptychographic system that help differentiate it from other coherent diffractive imaging methods were previously defined [88]. These definitions are also applicable to FP due to the reciprocity between the two procedures [72]. We restate those properties in the context of FP as follows:…”
Section: Parallels With Other Imaging Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In most previous versions of ptychography, both object and illumination were modeled as scalar quantities [21]. Their reconstructions could be performed simultaneously by phase retrieval algorithms, thanks to the diversity introduced by the ptychographic scan [22,23]. Here in comparison, the vectorial formalism of Eq.…”
Section: E(r)mentioning
confidence: 99%